Photoinduced decarboxylative azidation of cyclic amino acids. Issue 7 (9th January 2019) - Marcote, David C.; Street-Jeakings, Rosie; Dauncey, Elizabeth; Douglas, James J.; Ruffoni, Alessandro; Leonori, Daniele
Abstract : The direct decarboxylative azidation of cyclic α-amino acids has been achieved via visible light-mediated organo-photoredox catalysis. Abstract : The direct decarboxylative azidation of cyclic α-amino acids has been achieved via visible light-mediated organo-photoredox catalysis. This synthetic strategy allows the simple preparation of azide-contaning building blocks and has been used in the selective modification of N-terminal proline residues of two di-peptides.